(untitled) (UNED Research Journal, 2017)
Located in Costa Rica, Pacuare Nature Reserve has a long established history of wildlife monitoring programs primarily focused on species of nesting marine turtles and the Agami herons (Agamia agami) found within the reserve. Our research represents the first assessment on the local terrestrial mammal populations. Data was collected by using seven camera trap stations distributed within the boundaries of the reserve. From April 2015 to March 2016, and after a total of 1 643 camera trap nights, we were able to identify 11 terrestrial mammalian species distributed in six orders and nine families. The most abundant species was the common opossum (Didelphis marsupialis), followed by the ocelot (Leopardus pardalis). A noticeably absent species, otherwise common throughout the area, was the Central American agouti (Dasyprocta punctata). Our results are similar to those from other protected areas in the Northeastern Caribbean coast of Costa Rica.